2010
DOI: 10.5424/sjar/2010081-1141
|View full text |Cite
|
Sign up to set email alerts
|

The effects of melatonin on in vitro oocyte competence and embryo development in sheep

Abstract: The aim of this study was to assess the effects of melatonin on the in vitro maturation and fertilization of sheep oocytes, and on the in vitro culture of the embryos. Oocytes from sheep ovaries collected at the slaughterhouse were divided into four groups, two of which were treated with either 10E–5 M (M5) or 10E–6 M (M6) melatonin, while the other two groups served as untreated controls (C5 and C6). After in vitro fertilization with fresh ram semen, the embryos produced in each group were divided into two se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
2
13
0
3
Order By: Relevance
“…Contrary to our previous results (Soto‐Heras et al, ) we did not find a higher blastocyst yield with melatonin. Other studies neither found improvement on blastocyst production (Casao et al, ; Rodrigues‐Cunha et al, ; Takada, Martins Junior, Mingoti, Balieiro, & Coelho, ) which denotes a variability in results depending on specific culture conditions. However, we observed an increase on the ICM number and ICM:TE ratio in hatched blastocysts.…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to our previous results (Soto‐Heras et al, ) we did not find a higher blastocyst yield with melatonin. Other studies neither found improvement on blastocyst production (Casao et al, ; Rodrigues‐Cunha et al, ; Takada, Martins Junior, Mingoti, Balieiro, & Coelho, ) which denotes a variability in results depending on specific culture conditions. However, we observed an increase on the ICM number and ICM:TE ratio in hatched blastocysts.…”
Section: Discussionmentioning
confidence: 92%
“…For example, when melatonin was applied in the pig oocyte maturation medium, the rate of in vitro maturation of oocyte, parthenogenetic blastocyst embryos, and blastocyst cell number were significantly increased; these were accompanied by a substantial reduction in ROS in the melatonin‐treated embryos . It is reported that 10 −6 m melatonin also promoted the maturation rate and cleavage rate in sheep after in vitro fertilization . In addition to studies regarding melatonin's effects on oocytes, Pang et al.…”
Section: Introductionmentioning
confidence: 99%
“…antitumour activity (Zou et al., ), antioxidant protection (Ginther et al., ), enhances immune function (Srinivasan et al., ), sleep (Dawson & Encel, ) and reproduction (Reiter et al., )). Additionally, the melatonin as an antioxidant and free radical scavenger reduces the oxidative damage and dysfunction of oocytes during maturation (Casao et al., ; Tian et al., ) and embryo culture (Wang et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oxidative stress detection with direct or indirect measures such as ROS production, amount of intracellular GSH, DNA damage or gene expression could be used to develop and evaluate strategies to prevent or minimize oxidative dysfunction during embryonic development (Kwak et al., ; Mukherjee et al., ). Furthermore, the inclusion of antioxidants or free radical scavengers to the maturation (Casao et al., ; Tian et al., ) and culture medium (Wang et al., , ) may reduce oxidative stress and improve conditions for embryonic development.…”
Section: Introductionmentioning
confidence: 99%